Methods of teaching reading using English authentic texts for students of special faculties (on the material of the novel “Chronicles of Narnia” by C. Lewis) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
This paper deals with the modern approaches in teaching reading skills though authentic texts. It analyzes recent research covering the problem of using authentic materials in teaching foreign languages, English in particular. It also focuses on identifying the peculiarities of selecting authentic texts and its advantages of using them in the class. The paper sums up the key stages of teaching reading (pre-reading, while-reading and post-reading) as well. Moreover, this paper presents the set of tasks based on the fantastic novel “The Chronicles of Narnia: the Lion, the Witch and the Wardrobe” by C. S. Lewis. The choice of this fantastic novel as the main source of an authentic text is explained by the fact that this work contains numerous idiomatic expressions that reveal the cultural heritage and contribute to the acquisition of linguistic and cultural information. The work contains a great variety of descriptive parts that correspond to the thematic blocks of the academic course “Practical English Course of Second Language (English)”. It expands and consolidates the active vocabulary of students. The novel also represents an interesting interpretation of many religious and moral-ethical aspects of life, depicted on the background of fantastic events, which have a great impact on training future language teachers. These exercises are built according to the main stages of working with the authentic texts including pre-reading, while-reading and post-reading activities. These tasks focus on not only developing communicative skills, simultaneously training vocabulary and grammar, but also cover moral aspects of upbringing. They can be successfully applied as the part of an optional home reading course in terms of teaching the academic course “Practical course of the main language (English)”.
Keywords: teaching reading; authentic text; pre-reading; while reading; post-reading